Low power embedded software optimization for the NuttX RTOS - Sánchez-López, Diego (Instituto Tecnológico de Costa Rica, 2013)
This paper presents the study of the implementation for a new feature that allows the NuttX RTOS, handling the power consumption in order to optimize it. The project was focused on controlling different power states, following the global trend in portable devices. In this document, it’s explained all the necessary information that was necessary before to start developing all the modules, and also contains all the steps that were followed in order to get the final system. After this project, NuttX is able to handle 4 different power modes, this power modes were designed in order to reduce the power consumption gradually when the RTOS is idle, and also the system is able to return to its higher performance mode when it’s required. Part of the requirements in this project was to build a benchmark application in order to verify the functionality of this newfeature, in the document is explained not only how this application works, but also all the hardware used in order to acquire the data that were used in the analysis.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Electrónica, 2013
Keywords: NuttX RTOS; Consumo de energía; Dispositivos portátiles; Procesos